Current Trends and Predictors of Case Outcomes for Malpractice in Colonoscopy in the United States. Issue 1 (January 2022) - Patel, Krishan S.; Kothari, Pooja; Gantz, Owen; Prabhu, Arpan; Ayyaswami, Varun; Kono, Janelle; Ahlawat, Sushil
Abstract : Background: Over 14 million colonoscopies are performed annually, and this procedure remains the largest contributor to malpractice claims against gastroenterologists. The aim of this study was to evaluate reasons for litigation and predictors of case outcomes. Materials and Methods: Cases related to colonoscopy were reviewed within the Westlaw legal database. Patient demographics, reasons for litigation, case payouts, and verdicts were assessed. Multivariate regression was used to determine predictors of defendant verdicts. Results: A total of 305 cases were included from years 1980 to 2017. Average patient age was 54.9 years (range, 4 to 93) and 52.8% of patients were female. Juries returned defendant and plaintiff verdicts in 51.8% and 25.2% of cases, respectively, and median payout was 995, 000. Top reasons for litigation included delay in treatment (65.9%) and diagnosis (65.6%), procedural error (44.3%), and failure to refer (25.6%). Gastroenterologists were defendants in 71% of cases, followed by primary care (32.2%) and surgeons (14.8%). Cases citing informed consent predicted defendant verdict (odds ratio, 4.05; 95% confidence interval, 1.90-9.45) while medication error predicted plaintiff verdict (odds ratio, 0.18; 95% confidence interval, 0.04-0.59). Delay in diagnosis ( P =0.060) and failure to refer ( P =0.074) trended toward plaintiff verdict but did not reach significance. Most represented states were New York (21.0%), California (13.4%), Pennsylvania (13.1%), Massachusetts (12.5%). Conclusions: Malpractice related to colonoscopy remains a significant and has geographic variability. Errors related to sedation predicted plaintiff verdict and may represent a target to reduce litigation. Primary care physicians and surgeons were frequently cited codefendants, underscoring the significance of interdisciplinary care for colonoscopy.